NPS Model in Consumer Loyalty Measurement of Pejeruk Abian Tempeh - Ilhamudin, M.; Hilmiati, Hilmiati (Jurnal Multidisiplin Sahombu, 2025)
This research aims to find out the customer loyalty of Pejeruk Abian tempeh which is one of the products in the city of Mataram. The type of research is descriptive which is used to get an overview of customer loyalty which is an important aspect of consumer behavior theory. This study uses a sample survey method, by choosing several tempeh sales markets in the city of Mataram as the location of the research. The population in this study is all customers of tempeh products who come to make purchases in that market. The respondent determination technique used in this study is purposive sampling, which is sampling according to the purpose of the research. Since the number of members of the research population is not known exactly, it was determined that the sample taken for the study was 100 people. The analysis uses the Net Promoter Score (NPS) model, which is a method to measure and understand customer loyalty levels. The results of the study show that the loyalty of consumers of Pejeruk Abian tempeh products is very loyal. These results were obtained from the process of analyzing a number of attributes inherent in the product's taste, price, aroma, texture, and nutritional content. The high customer perception of the quality of the performance of the tempe product makes customers recommend the product to their friends or colleagues. This value of loyalty needs to be maintained and improved by marketers to ensure the survival of the business in the future.